Antimicrobial peptide LL-37 ameliorates a murine sepsis model via the induction of microvesicle release from neutrophils. Issue 7 (October 2020) - Kumagai, Yumi; Murakami, Taisuke; Kuwahara-Arai,; Iba, Toshiaki; Reich, Johannes; Nagaoka, Isao
Sepsis is a life-threatening disease caused by systemic dys-regulated inflammatory response to infection. We previously revealed that LL-37, a human cathelicidin antimicrobial peptide, improves the survival of cecal ligation and puncture septic mice. Ectosomes, microvesicles released from neutrophils, are reported to be elevated in sepsis survivors; however, the functions of ectosomes in sepsis remain largely unknown. Therefore, we herein elucidated the protective action of LL-37 on sepsis, by focusing on LL-37-induced ectosome release in a cecal ligation and puncture model. The results demonstrated the enhancement of ectosome levels by LL-37 administration, accompanied by a reduction of bacterial load. Importantly, ectosomes isolated from LL-37-injected cecal ligation and puncture mice contained higher amounts of antimicrobial proteins/peptides and exhibited higher antibacterial activity, compared with those from PBS-injected cecal ligation and puncture mice, suggesting that LL-37 induces the release of ectosomes with antibacterial potential in vivo . Actually, LL-37 stimulated mouse bone-marrow neutrophils to release ectosomes ex vivo, and the LL-37-induced ectosomes possessed antibacterial potential. Furthermore, administration of LL-37-induced ectosomes reduced the bacterial load and improved the survival of cecal ligation and puncture mice. Together these observations suggest LL-37 induces the release of antimicrobial ectosomes in cecal ligation and puncture mice, thereby reducing the bacterial load and protecting mice from lethal septic conditions.